Art for Obama: Designing Manifest Hope and the Campaign for Change - Fairey Shepard (Abrams Image, 2009)
Few events in recent memory have captivated the world’s attention like that of Barack Obama’s historic presidential campaign. Not only did it stir passionate political momentum, but it also inspired the creative talents of a world of artists, illustrators, and graphic designers.